CuO urchin-nanostructures synthesized from a domestic hydrothermal microwave method - Keyson, D.; Volanti, D. P. [UNESP]; Cavalcante, L. S.; Simões, Alexandre Zirpoli [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
This letter reports the synthesis of CuO urchin-nanostructures by a simple and novel hydrothermal microwave method. The formation and growth of urchin-nanostructures is mainly affected by the addition of polyethylene glycol (PEG). The hierarchical malachite particles are uniform spheres with a diameter of 0.7-1.9 mu m. CuO urchin-nano structures were characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FEG-SEM) and nitrogen adsorption (BET). The specific surface area of the CuO nanostructured microspheres was about 170.5 m(2)/g. A possible mechanism for the formation of such CuO urchin-nanostructures is proposed. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: oxides; chemical synthesis; electron microscopy